PROGRAM GURU AYO MENULIS!!! UPAYA PENINGKATAN KOMPETENSI PROFESIONAL GURU MELALUI PENYUSUNAN INSTRUMEN PENILAIAN AUTENTIK - Wicaksana, Muhlis Fajar (Jurnal Terapan Abdimas, 2021)
Abstract. The authentic assessment system in applying the 2013 curriculum is one of the problems faced by Indonesian language teachers in Sukoharjo. Various problems arise in the hope of this authentic assessment. The purpose of this activity is: 1) fostering the enthusiasm of Indonesian language education teachers to develop their competence in the field of preparing authentic assessment instruments; 2) provide insights into knowledge about developing authentic assessment instruments; 3) introduce and assist teachers in developing authentic assessment instruments. The detailed training is divided into several activities, namely: (1) Presentation on the authentic assessment system and its characteristics; (2) Discussion of various problems in the application of authentic assessment; (3) assisting the teacher in preparing the assessment instrument for Indonesian subjects. After conducting a series of training, participants learned the importance of developing professional competence of teachers through the preparation of authentic assessment instruments. The participants were very enthusiastic about asking questions and discussing after the speakers gave their material. Most participants asked about alternative solutions to the problems faced in applying authentic assessment. It is hoped that from the training on the preparation of this authentic assessment instrument, Indonesian language teachers will no longer experience difficulties in preparing the assessment instruments. Abstrak. Sistem penilaian autentik pada penerapan kurikulum 2013 menjadi salah satu permasalahan yang dihadapi oleh guru bahasa Indonesia di Sukoharjo. Berbagai permasalahan muncul pada penarapan penilaian autentik ini. Tujuan kegiatan ini adalah 1) menumbuhkan semangat guru pendidikan bahasa Indonesia untuk mengembangkan kompetensinya dalam bidang penyusunan instrumen penilaian autentik; 2) memberikan wawasan pengetahuan tentang pengembangan instrumen penilaian autentik; 3) mengenalkan dan membantu guru dalam menyusun instrumen penilaian autentik. Pelaksanaan pelatihan secara terperinci dibagi menjadi beberapa kegiatan yaitu: (1) Presentasi tentang sistem penilaian autentik dan karakteristiknya; (2) Diskusi tentang berbagai permasalahan-permasalahan pada penerapan penilaian autentik; (3) mendampingi guru dalam menyusun instrumen penilaian mata pelajaran bahasa Indonesia. Setelah melakukan serangkaian pelatihan, peserta mengetahui arti penting pengembangan kompetensi profesional guru melalui penyusunan instrumen penilaian autentik. Para peserta sangat antusias bertanya dan berdiskusi setelah pemateri menyampaikan materinya. Sebagian besar peserta bertanya tentang solusi alternatif dalam permasalahan yang dihadapai pada penerapan penilaian autentik. Diharapkan dari pelatihan penyusunan instrumen penilaian autentik ini, guru bahasa Indonesia tida lagi mengalami kesulitan dalam menyusun instrumen penilaian.